2022
DOI: 10.1200/jco.2022.40.16_suppl.4070
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes for the phase 3 TOPAZ-1 study of durvalumab plus gemcitabine and cisplatin in advanced biliary tract cancer.

Abstract: 4070 Background: TOPAZ-1 (NCT03875235) is a randomized, double-blind, global, Phase 3 study evaluating the efficacy and safety of durvalumab (D) in combination with (+) gemcitabine and cisplatin (GC) as first-line treatment for patients (pts) with advanced biliary tract cancer (BTC).1 D + GC significantly improved overall survival (OS) versus placebo (PBO) + GC and represents a new treatment option. Methods: A pre-planned secondary objective of TOPAZ-1 was to assess pt-reported outcomes (PROs) for pts receivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Quality of life (QOL) was similar for both arms, as well. 91 Results of the safety analysis were consistent with prior studies and similar between treatment groups, and give comfort to treating with the IO and chemotherapy TOPAZ-1 regimen in terms of tolerability.…”
Section: Immunotherapeutic Approaches For Btcsupporting
confidence: 82%
“…Quality of life (QOL) was similar for both arms, as well. 91 Results of the safety analysis were consistent with prior studies and similar between treatment groups, and give comfort to treating with the IO and chemotherapy TOPAZ-1 regimen in terms of tolerability.…”
Section: Immunotherapeutic Approaches For Btcsupporting
confidence: 82%
“…Additionally, a subsequent analysis of the TOPAZ-1 trial analyzed time to deterioration via patient reported outcomes using multiple quality-of-life questionnaires. 30 The study found that the addition of durvalumab to gemcitabine plus cisplatin did not result in a significant difference in time to deterioration with regards to patient quality-of-life or function. Overall, this demonstrates that the addition of durvalumab was well tolerated.…”
Section: Durvalumab In Advanced Biliary Tract Cancermentioning
confidence: 90%
“…Immune-mediated adverse event was found in 12.7% of patients who received additional durvalumab, including 2.4% of patients with grade 3–4 event, and 0.9% of patients discontinuing the treatment due to adverse events [ 88 ]. In the quality-of-life investigation, there was no difference between the GemCis group and durvalumab plus GemCis group [ 89 ]. From the exploratory analysis, the efficacy and safety outcomes were similar across different regions (Asia vs. others) and primary tumor location (IHCCA vs. EHCCA vs. GBCA) [ 90 , 91 ].…”
Section: Immunotherapymentioning
confidence: 99%